An Unusual Coexistence of Primary Central Nervous System Non-Hodgkin’s Lymphoma and Acute Promyelocytic Leukemia - Fracchiolla, Nicola Stefano; Sciumè, Mariarita; Cernuschi, Giulia; Cortelezzi, Agostino (Case Reports in Hematology, 2018)
Acute promyelocytic leukemia and primary central nervous system lymphoma are uncommon hematological malignancies. The co-occurrence of acute myeloid leukemia with various lymphoproliferative diseases is an extremely rare condition, especially in the absence of previous chemotherapy or radiotherapy. Herein, we provide a comprehensive characterization of a patient with concomitant diagnosis of extranodal high-grade non-Hodgkin B-cell neoplasm confined to the central nervous system and acute promyelocytic leukemia. We describe the efficacy and feasibility of the consecutive use of all-trans retinoic acid and arsenic trioxide-containing regimen for the treatment of promyelocytic leukemia and high-dose methotrexate plus cytarabine to treat lymphoproliferative involvement of the central nervous system.